Strategies for managing risk in work-integrated learning: A New Zealand perspective - Fleming J; Hay K (Work-Integrated Learning New Zealand)
The immersion of students into a workplace environment, as part of a deliberate pedagogy for integrating theoretical and practical knowledge, is not without risk. In order to safely provide such work-integrated learning (WIL) opportunities, the responsibility for managing these risks should be shared by all stakeholders. The purpose of this study was to explore strategies to manage different types of risks in WIL for students, host organizations and universities. Data was collected using an online survey, and interviews with university staff involved in WIL. Twenty-eight disciplines and a range of models of WIL from across the eight New Zealand universities were represented. Key strategies identified included: appropriate pre-placement preparation for students and hosts; clear contractual arrangements; good internal systems and resourcing (especially staff); and strong relationship management. Practical guidelines to help WIL stakeholders further develop their understanding and awareness of risk are presented.
The International Journal of Work-Integrated Learning is an Open Access journal which means that all content is freely available without charge to the user or his/her institution. Users are allowed to read, download, copy, distribute, print, search, or link to the full texts of the articles, or use them for any other lawful purpose, without asking prior permission from the publisher or the author.